Stable Ta2O5 Overlayers on Hematite for Enhanced Photoelectrochemical Water Splitting Efficiencies. Issue 3 (27th November 2017) - Forster, Mark; Potter, Richard J.; Yang, Yi; Li, Yat; Cowan, Alexander J.
Abstract: Hematite (α‐Fe2 O3 ) is one of the most promising photoanodes for water oxidation, however the efficiencies of current hematite materials remain low. Surface trap states are often reported as one of the factors which limit the activity of hematite photoelectrodes, often leading to undesirable surface pinning and trap‐mediated recombination. The deposition of ultra‐thin Al2 O3 overlayers is known to enhance hematite activity through passivation of surface states, however Al2 O3 is rapidly degraded at normal hematite operating pH values (pH≈13). This study reports atomic layer deposition (ALD) of Ta2 O5 thin films as stable, passivating overlayers on a range of hematite photoelectrodes and demonstrates that enhanced activity correlates with observed changes in trap‐state dynamics. Abstract : Protective layers : Tantalum pentoxide (Ta2 O5 ) is deposited by atomic layer deposition onto a range of hematite (α‐Fe2 O3 ) photoelectrodes for water splitting. The stable Ta2 O5 passivating layer reduces electron trapping and improves photoactivity.